2023
DOI: 10.1177/26323524231156944
|View full text |Cite
|
Sign up to set email alerts
|

‘The beauty and the less beautiful’: exploring the meanings of dying at ‘home’ among community and practitioner representatives and advocates across Canada

Abstract: Background: Significant structural and normative pressures privilege the ideal of dying at home in Canada. At the same time, the social complexities and meanings associated with dying in particular locations remain critically unexamined. Objective: The aim of this study is to explore how diverse community members, including health and social care stakeholders, talk about preferences for locations of dying, with a particular focus on meanings of dying at home. Design: Semi-structured virtual interviews were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For example, social imaginaries often include home as an indicator of the ‘good death’. This does not account for how political as well as social and cultural factors influence where people are cared for and die 13,14▪ . The ‘good death’ as ‘home death’ script problematises the value of dying somewhere other than home.…”
Section: Resultsmentioning
confidence: 99%
“…For example, social imaginaries often include home as an indicator of the ‘good death’. This does not account for how political as well as social and cultural factors influence where people are cared for and die 13,14▪ . The ‘good death’ as ‘home death’ script problematises the value of dying somewhere other than home.…”
Section: Resultsmentioning
confidence: 99%
“…As part of a larger mixed methods project studying preferences for and meanings of dying at home in Canada (Chan et al, 2023; Funk et al, 2022; Funk et al, 2023), we identified public policy related to dying at home (including both palliative and end‐of‐life care) within written documentation in which the federal and provincial/territorial governments state public directives for the health care system. This included 12 policies or formal statements, 19 websites, 15 action/strategic plans, and 13 bilateral health agreements (Table 1).…”
Section: Methodology and Designmentioning
confidence: 99%